ASSESSMENT OF AGROCHEMICALS USAGE ON THE JOS PLATEAU, NIGERIA: PROBLEMS AND PROSPECTS - P.Z., Chuwang,; E.A, Salako, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The application of agrochemicals on the Jos Plateau has become imperative as farm labour has drastically reduced and pests and have increasingly ravaged farms. This study was undertaken to determine the factors that militate against the successful utilization of agrochemicals by farmers. Results indicate that 28% of the farmers have used agrochemicals for over 30years. This long usage without scientific approach could have resulted in some pests and weeds developing resistance to the agrochemicals as pesticide ineffectiveness was reported by farmers. Pesticide poisoning, killing of non-target organisms, drifts and application difficulties have been cited as problems experienced by farmers. Suggestions to remedy these problems experienced by farmers include proper education on the best methods of pesticide application and regulation of pesticides supplied to farmers. We believe that a detailed study of the pesticides (along with laboratory analysis) and exploration of the botanical pesticides in the communities needs to be undertaken